Padrões de escoamento do vento na região metropolitana de Maceió - Maia, Ruany Gomes Xavier (2016)
The wind flow study in an urban environment is of great importance in many areas, not limited only to the Meteorology. Maceio currently lies in accelerated process of demographic and urban expansion. However, urban public policies in the city are scarce. The particular conditions of the urban environment substantially modify the local climate, creating a particular urban climate through complex changes in the surface. Faced with the need to understand the relationship between the wind climatology of Maceió and its relation to the urban environment, it was prepared an overview of the wind flow in the city, taking into account the influence that the urban environment plays in this process. From a series of 10 years of data (2003-2012), the characteristics of wind direction and speed were analysed through statistical analysis and use of microscale model. It was found that the large-scale circulation of the trade winds and the local-scale circulation of sea and land breezes govern the wind regime in Maceió. The occurrence of urban breezes was also observed. The winds are predominantly from E and SE, which varies seasonally according to the positioning of the South Atlantic Subtropical High throughout the year. Its direction also varies in daily cycles, with a predominance of winds from E during the day and N and NE winds during the night along the dry season. In the rainy season, SE winds prevail during the day and W and NW at night. The intensity of the winds also varies seasonally and daily, being stronger in the dry season and during the day and milder in the rainy season and at night. In microscale model WAsP, spatial analysis of the wind was made and it was analysed the influence of city topography and roughness in its average flow. It was observed that the greater roughness of the city exerts a braking effect on the wind that reaches the coast. In some areas, the topography caused acceleration in wind speed. There were wind stagnation areas between the lower and upper part of the city and in the valleys that intersperse the uptown.